Polyphyllin I Ameliorates Collagen-Induced Arthritis by Suppressing the Inflammation Response in Macrophages Through the NF-κB Pathway - Wang, Qiong; Zhou, Xin; Zhao, Yongjian; Xiao, Jun; Lu, Yao; Shi, Qi; Wang, Yongjun; Wang, Hongyan; Liang, Qianqian (Frontiers in Immunology, 2018)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder, characterized by an increased number of M1-like macrophages in the joints. Polyphyllin I (PPI), one of the main components in the Rhizoma of Paris polyphyllin, displays a selective inhibitory effect on various tumor cells. Here we sought to investigate the anti-rheumatoid arthritis effects and mechanisms of PPI on macrophages in vivo and in vitro. Materials and methods: In vitro, BMMs and PEMs were stimulated by LPS and IFN-γ and then treated with PPI. We determined the degree of activation of IKKα/β and p65, two key mediators of the NF-κB-mediated inflammatory pathway, by measuring their phosphorylated forms by Western blot. The p65 nuclear localization was detected by immunofluorescent staining. Further, a NF-κB-linked luciferase reporter plasmid, as well as those expressing key mediators of the Toll-like receptor 4 pathway, such as MYD88, IRAK1, TRAF6, TAK1 and p65, were used to identify the mechanism by which PPI achieves its inhibitory effects on macrophage-mediated inflammation. Moreover, a NF-κB inhibitor, p65-targeted siRNAs and a p65 plasmid were further used to validate the anti-inflammatory mechanism of PPI. In vivo, PPI (1 mg/kg) was administered intragastrically once a day for 7 weeks starting on the 42nd day after the first immunization with collagen in a collagen-induced arthritis (CIA) mouse model. Micro-computed Tomography scanning, histological examination, F4/80 and iNOS double immunofluorescent staining and CD4 immunohistochemical staining were performed to determine the effect of PPI treatment on joint structure and inflammation in this model. Results: PPI reduced the inflammatory cytokines production of PEMs stimulated by LPS/IFN-γ, inhibited the phosphorylation of IKKα/β and p65, and prevented p65 nuclear localization. The NF-κB luciferase assay showed that the target of PPI was closely related to the NF-κB pathway. Moreover, NF-κB inhibition, siRNA-mediated knockdown of p65 and p65 overexpression eliminated PPI’s inhibitory effect. In addition, PPI attenuated the bone erosion and synovitis, as well as M1-like macrophage and T cell infiltration, in the ankle joint of the CIA model. Conclusion: PPI demonstrated effective amelioration of synovial inflammation in the ankle joint of CIA mice while suppressing NF-κB-mediated production of pro-inflammatory effectors in activated macrophages.